Comportamento térmico de compostos ciclopaladados binucleares contendo azo-ligantes aniônicos - De Almeida, Eduardo Tonon [UNESP]; Mauro, Antonio Eduardo [UNESP]; Santana, Anderson Martinez [UNESP] (My University, 2002)
This paper deals with the thermal behavior study of cyclopalladated complexes obtained from reactions of [Pd(dmba)N3l2 (1), dmba = N,N-dimethylbenzylamine, with azole-compunds, such as, the anionic ligands pyrazolate (pz), imidazolate (imz) and 3.5-dimethyl-pyrazolate (3.5-dmpz). The characterization of the binuclear complexes [Pd(dmba)(μ-pz)]2 (2), [Pd(dmba)(μ-imz)]2 (3) and [Pd(dmba)(μ-3.5-dmpz)]2 (4) was carried out by elemental analysis, IR and NMR spectroscope Their thermal behaviour has been investigated and the final product was identified by X-ray powder diffractometry which showed the formation of Pd(0) as final decomposition product.
Thermal behaviour of binuclear cyclopalladated compounds containing anionic azo-ligands
Keywords: 3,5-dimethyl-pyrazolate; Cyclopalladated; Imidazolate; Pyrazolate; Thermal analysis